Islamic Identity in Aceh Shaped by the Historical and Cultural Heritage of the Perlak Sultanate - Usman; Rahman, Aulia; Riyani, Mufti; Shamadiyah, Nurasih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2024)
Studies on the role of the Peureulak Sultanate in Islamization in Indonesia still need to be completed. By conducting this research, this research can fill the knowledge gap about the role and contribution of the Peureulak Sultanate in the Islamization process in Indonesia. Apart from that, this research is important in the context of strengthening Islamic identity in Aceh. Through analysis of historical evidence, this research will look at and analyze how the role of the Peureulak Sultanate influenced and shaped Islamic identity in Aceh. This can help preserve and strengthen the Acehnese people's cultural identity, which is closely related to Islam. By reviewing the role of the Peureulak Sultanate in Islamization in Indonesia, we can view this process from a more holistic perspective. This study pays attention to historical, social, cultural, and identity aspects so that we can understand the Islamization process comprehensively and contextually. This research is historical. The research was carried out by conducting literature studies, document and archive studies, in-depth interviews with local figures in Perlak, conducting field studies at heritage sites of the Perlak sultanate (graves of the Perlak kings, ancient harbor, Perlak River), and conducting historical analysis. The findings from this research reveal that the Perlak Sultanate has a rich historical heritage, especially in the form of the tombs of the Perlak kings, which played an important role in strengthening Islamic identity in Aceh. The Perlak Sultanate also played a role in the pepper trade, which, through trade routes, helped spread Islam. The pepper trade not only creates economic wealth but also brings positive changes in the culture and society, with values such as brotherhood, tolerance, mutual respect and respect becoming a strong foundation. The results of this research provide in-depth insight into the historical role of the Perlak Sultanate in the formation of Islamic identity in Aceh and the importance of factors such as trade in this process. This study makes a valuable contribution to understanding Aceh's diverse history and culture.